7-Acetoxycoumarin Inhibits LPS-Induced Inflammatory Cytokine Synthesis by I kappa B alpha Degradation and MAPK Activation in Macrophage Cells - Park, Taejin; Park, Jin-Soo; Sim, Ji Han; Kim, Seung-Young (MDPI, 2020)
Acetylation involves the chemical introduction of an acetyl group in place of an active hydrogen group into a compound. In this study, we synthesized 7-acetoxycoumarin (7AC) from acetylation of umbelliferone (UMB). We examined the anti-inflammatory properties of 7AC in lipopolysaccharide (LPS)-treated RAW 264.7 macrophage cells. The anti-inflammatory activity of 7AC on viability of treated cells was assessed by measuring the level of expression of NO, PGE(2)and pro-inflammatory cytokines, namely interleukin-1 beta (IL-1 beta), interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-alpha) in 7AC-treated RAW 264.7 macrophages. The 7AC was nontoxic to cells and inhibited the production of cytokines in a concentration-dependent manner. In addition, its treatment suppressed the production of pro-inflammatory cytokines in a dose-dependent manner and concomitantly decreased the protein and mRNA expressions of inducible NO synthase (iNOS) and cyclooxygenase-2 (COX-2). Moreover, the levels of the phosphorylation of mitogen-activated protein kinase (MAPK) family proteins such as extracellular signal-regulated kinase (ERK), c-JunN-terminal kinase (JNK), p38 and nuclear factor kappa B (NF-kappa B) were reduced by 7AC. In conclusion, we generated an anti-inflammatory compound through acetylation and demonstrated its efficacy in cell-based in vitro assays.
Keywords: NITRIC-OXIDE; TNF-ALPHA; UMBELLIFERONE; METABOLISM; EXPRESSION; INDUCTION; MECHANISM; INNATE; KINASE; INOS